TYPE-I TYMPANOPLASTY BY UNDERLAY TECHNIQUE - FACTORS AFFECTING OUTCOME - Sajid, Tahira; Shah, Mohammad Imran; Ghani, Rehman; Asif, Mohammad (Journal of Ayub Medical College Abbottabad, 2017)
Background: Type-I Tympanoplasty is an operation which is widely done to close a persistent tympanic membrane perforation after clearing the disease from the middle ear. It is very safe and effective procedure. The success rate varies in different setups and there are some confounding factors which affect the result of Type-I tympanoplasty like the size, type and location of perforation. By conducting this study, we aimed to calculate the success rate of Type-I Tympanoplasty in Ayub Teaching Hospital and assess which confounding factors affect the success rate. Methods: This case series study was conducted at Ayub teaching hospital from 1st January 2014 to 31st December 2015. All the patients who presented with dry ears, no nasal disease and persistent tympanic membrane perforations during this period were operated upon and overall success rate was calculated. In addition, the relationship between the site of perforation, size of perforation and the type of perforation and the success rate of Type-I Tympanoplasty was also calculated. Results: One hundred and thirteen patients were included in this study. Out of these 91 (80.5%) showed complete healing after surgery. Anterior perforations were found to fail the procedure in 41.7% of the cases, while central perforation failed in only 5.4% of the cases. In cases of marginal perforations healing was significantly decreased, i.e., only 47.1% while it was 94.9% in cases where annulus was not involved. Larger perforations also showed poor surgical outcome. 100% of the small perforation healed completely while only 58.3% of the large perforations showed successful result after surgery. When p-value was calculated all of these findings were more than 95% significant. Conclusion: There is a significant association between the healing of tympanic membrane after Type-I Tympanoplasty and site, size and type of perforation. Anterior perforations, marginal perforation and large perforations reduce the chances of successful outcome of Type-I Tympanoplasty. Keywords: Type-I Tympanoplasty; size of perforation; site of perforation; outcome percentages